PEMBINAAN PENGENALAN BASIC ENGLISH CONVERSATION AT THE AIRPORT KEPADA STAF BANDARA HANG NADIM BATAM - Robby Satria; Nurma Dhona Handayani; Ellbert Hutabri (PUAN INDONESIA, 2022)
English is an international language which is very important for smooth bilingual interaction. Along with the times, the ability to speak English is required in all aspects of life to develop. One that is experiencing rapid development is the air transportation industry, which has a similar impact on the development of the airport aspect as a facility for providing aircraft transportation services. One of the important airports in the Riau Archipelago is Batam's Hang Nadim Airport. The airport was officially opened to the public on January 1, 1995 under the name "Hang Nadim International Airport. Since then until today, Hang Nadim airport has grown rapidly and has become one of the largest and busiest airports in Sumatra. With the rapid development of Hang Nadim Airport This, of course requires the use of an international language, namely English as the most commonly used communication medium. It has become a must for airport staff to be able to master English for the smooth operation of the technical process of aircraft and air flight systems. All airport workers are required to have good English language skills. it is appropriate to create conducive working conditions, but in reality on the ground, not all staff who work at airports have basic English skills, especially regarding the basic conversation part in English at the airport. If they are not equipped with basic English skills then they will not be able to speak English. can work optimally. Therefore, it is very important to initiate a dedication to provide a basic introduction to English for staff at Hang Nadim Airport, Batam City, Riau Islands.